Association between porphyria cutanea tarda and beta-thalassemia major - Barbieri, L; Macrí¬, A; Lupia Palmieri, G; Aurizi, C; Biolcati, G (Cellular and Molecular Biology, 2009)
The paper describes the first two cases of porphyria cutanea tarda associated with beta-thalassemia major. The clinical course of two female patients affected by beta-thalassemia major was complicated by the onset of porphyria cutanea tarda. Both patients were also suffering from hepatitis C virus infection, iron overload and anemia. We discuss about the role performed by some of these conditions in triggering overt porphyria cutanea tarda. An improvement of the clinical and biochemical picture of porphyria cutanea tarda in both patients was obtained with chloroquine therapy given that their chronic anemia did not permit phlebotomy.